Determinan health locus of control pada pasien diabetes mellitus tipe 2 - Nurjaman, Iman; Jinan, Ridwan Riadul; Sutrisno, Nisa Wening Asih; Sumarni, Nining; Nurulhuda, Aziz's (Holistik Jurnal Kesehatan, 2025)
Background: Diabetes mellitus (DM) is a growing public health issue in Indonesia, with West Java ranking 17th in prevalence. Many patients still exhibit low self-control in managing their condition. Purpose: To identify determinants of health locus of control (HLoC) among patients with type 2 DM at the Outpatien Unit of dr. Slamet Regional Public Hospital Garut. Method: A cross-sectional analytical survey was conducted among 103 patients using structured questionnaires assessing knowledge, attitude, motivation, and family support. Data were analyzed using Chi-square and logistic regression tests. Results: Significant associations were found between HLoC and attitude (p = 0.020), motivation (p = 0.001), and family support (p = 0.011), while knowledge showed no significant relationship (p = 0.074). Motivation emerged as the strongest determinant of HLoC (p = 0.001; OR = 5.379; 95% CI = 2.065–14.015). Conclusion: Motivation plays a key role in shaping the HLoC among type 2 DM patients. Those with higher motivation were over five times more likely to exhibit a strong internal HLoC. Strengthening patient motivation through education and empowerment strategies is essential to foster better self-management and outcomes in diabetes care.   Keywords: Diabetes Mellitus; Health Locus of Control; Motivation; Patient Empowerment; Self-Control.   Pendahuluan: Diabetes melitus (DM) merupakan masalah kesehatan masyarakat yang terus meningkat di Indonesia, dengan Provinsi Jawa Barat menempati peringkat ke-17 dalam hal prevalensi. Banyak pasien masih menunjukkan kontrol diri yang rendah dalam mengelola kondisinya. Tujuan: Untuk mengidentifikasi determinan health locus of control (HLoC) pada pasien diabetes melitus tipe 2. Metode: Penelitian ini menggunakan desain survei analitik cross-sectional terhadap 103 pasien dengan menggunakan kuesioner terstruktur yang menilai pengetahuan, sikap, motivasi, dan dukungan keluarga. Data dianalisis menggunakan uji Chi-square dan regresi logistik. Hasil: Ditemukan hubungan yang signifikan antara HLoC dengan sikap (p = 0.020), motivasi (p = 0.001), dan dukungan keluarga (p = 0.011), sementara pengetahuan tidak menunjukkan hubungan yang signifikan (p = 0,074). Motivasi muncul sebagai determinan terkuat dari HLoC (p = 0.001; OR = 5.379; 95% CI = 2.065–14.015). Simpulan: Motivasi memegang peran kunci dalam membentuk HLoC pada pasien DM tipe 2. Pasien dengan motivasi tinggi memiliki kemungkinan lebih dari lima kali lipat untuk memiliki HLoC internal yang kuat. Penguatan motivasi pasien melalui strategi edukasi dan pemberdayaan sangat penting untuk mendorong pengelolaan diri yang lebih baik dan hasil perawatan diabetes yang optimal.   Kata Kunci: Diabetes Mellitus; Health Locus of Control; Motivasi; Pemberdayaan Pasien; Pengendalian Diri.